Neoadjuvant chemoradiotherapy for esophageal cancer: Impact on extracapsular lymph node involvement - Metzger, Ralf (The WJG Press and Baishideng, 2010)
AIM: To assess the effects of neoadjuvant chemoradiotherapy (CRT) on the presence of extracapsular lymph node involvement (LNI) and its prognostic value in patients with resected esophageal cancer. METHODS: Two hundred and ninety-eight patients with advanced esophageal cancer underwent esophagectomy between 1997 and 2006. One hundred and ninety patients (63.8%) were treated with neoadjuvant CRT prior to resection. A total of 986 metastatic LNs were examined. Survival of the patients was analyzed according to intra- and extra-capsular LNI. RESULTS: Five-year survival rate was 22.5% for the entire patient population. Patients with extracapsular LNI had a 5-year survival rate of 16.7%, which was comparable to the 15.8% in patients with infiltrated nodes of the celiac trunk (pM1lymph). In contrast to patients treated with surgery alone, neoadjuvant therapy resulted in significantly (P = 0.001) more patients with pN0/M0 (51.6% vs 25.0%). In 17.6% of the patients with surgery alone vs 16.8% with neoadjuvant CRT, extracapsular LNI was detected. Neoadjuvant therapy does not reduce the occurrence of extracapsular LNI. CONCLUSION: Extracapsular LNI is an independent negative prognostic factor not influenced by neoadjuvant CRT. In a revised staging system for esophageal cancer, extracapsular LNI should be considered.